The Methods of Modern Scholars in Interpretation: An Analytical Study - Ghanm Hameed Ibrahim; Idrees Qader Hamadameen (Zanco Journal of Humanity Sciences)
The Holy Qur’an is marvelous in its characteristics and features, rich in its meanings and connotations, precious in its treasures and facts, continuous in its giving. It was developed by the scholars of the ancestors of the nation, but the owners of the contemporary interpreters follow a Western philosophical method and rules in contemporary interpretation. They do not rely on language, nor on impact, neither on reason, nor on transmission, and they follow what is similar from the Qur’an in order to seek sedition and to seek its interpretation and distortion. So they went on to say in the methodology of contemporary interpretation that the origin in speech is interpretation, in that the Qur’an is a historical linguistic text like any other text, so it can be interpreted according to the requirements of the present era, so understanding its verses is determined from reality - i.e. from the needs of the age and human endeavors -, so the multiplicity of readings indicates On the strength of the text and its potential, the reader has the right to be creative in his reading of the text without anyone’s authority. And the scope for interpreting the text according to its circumstances and tendencies, until it came to transforming the text from revelation to interpretation so that this makes the Qur’an a text open to all meanings, so no interpretation or interpretation can close it permanently. But the principle of speech according to the commentators of the predecessors and successors is to interpret it as it appears, and it is not dispensed with except with a correct exchange. Some of the contemporary interpreters denied the synonymy in the Arabic language, and argued that the words served the meanings, and that the synonyms are nothing more than a deception. From re-understanding and developing it, this language is no longer able to express its renewed contents according to the requirements of the times, and that the terms and vocabulary of this language have lost their original significance due to the age of their use, as it descends the status of archaeological remains, from this point of view they interpret the Qur’anic vocabulary with interpretations that have not previously been explained, and from any explainer.